Creating a community of praxis: integrating global citizenship and development education across campus at University College Cork. (13th December 2022) - Cotter, Gertrude; Bonenfant, Yvon; Butler, Jenny; Caulfield, Marian; Prestwich, Barbara Doyle; Griffin, Rosarii; Khabbar, Sanaa; Mishra, Nita; Hally, Ruth; Murphy, Margaret; Murphy, Orla; O'Sullivan, Maeve; et al.
Abstract : The Praxis Project, established at University College Cork (UCC), Ireland, in 2018, seeks to assess possible models of best practice with regard to the integration of global citizenship and development education (GCDE) into a cross-disciplinary, cross-campus, interwoven set of subject area pedagogies, policies and practices. This study – the first part of an eventual three-part framework – asserts that the themes, theories, values, skills, approaches and methodologies relevant to transformative pedagogical work are best underpinned by ongoing staff dialogue in order to build communities of support around such systemic pedagogical change. This article is based on a collaborative study with the first cohort of UCC staff (2020–1), which demonstrates many ways in which staff and students realised that smaller actions and carefully directed attention to specific issues opened doors to transformative thinking and action in surprising ways. From this viewpoint, the striking need emerged for taking a strategic approach to how GCDE is, and should be, integrated into learning across subject areas.